Effects of osmolytes on salt resistance of Halomonas socia CKY01 and identification of osmolytes-related genes by genome sequencing - Park, Ye Lim; Choi, Tae Rim; Han, Yeong Hoon; Song, Hun Suk; Park, Jun Young; Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Kwon Young; Kim, Yun Gon; Yang, Yung Hun (Journal of Biotechnology, 2020)
Bacteria from the genus Halomonas hold promise in biotechnology as sources of salt-tolerant enzymes, biosurfactants, biopolymers, osmolytes, and as actors in bioremediation processes. In a previous work, we have identified Halomonas socia strain CKY01 having various hydrolase activities. Here, we aimed to study the survival strategies of marine bacteria. A deep genome sequencing study of H. socia CKY01 has revealed 4627 genes reaching 4,753,299 bp with 64 % of GC content. This strain produced polyhydroxybutyrate (PHB) having one gene clusters having phaC and phasin, and it has several genes responsible for the uptake, synthesis, and transport of the osmolytes such as betaine, choline, ectoine, carnitine, and proline in the bacterial genome. The addition of 60 mM glutamate, 60 mM proline and 60 mM ectoine enhanced growth 300.8 %, 294.2 % and 235.0 %, respectively, under 10 % saline conditions. In particular, ectoine and proline increased salt resistance and allowed cells to survive in more than 15 % NaCl. By combining experimental and genome sequencing data, we have investigated the importance of osmolytes on the survival of this Halomonas strain.
Keywords: Bacterial genomes; Bio-surfactants; Genome sequencing; Hydrolase activities; Marine bacterium; Polyhydroxybutyrate; Saline conditions; Salt resistance; Halomonas strain; Osmolytes; Salt tolerance; Whole genome sequencing